Authorea
DOI: 10.22541/au.158082947.75232617
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation curves of environmental DNA sequences predict coastal fish diversity in the Coral Triangle

Abstract: Environmental DNA (eDNA) has the potential to provide more comprehensive biodiversity assessments particularly for vertebrates in species-rich regions. Yet, this method requires the completeness of a reference database, i.e. a list of DNA sequences attached to each species, which is never met. As an alternative, a diversity of Operational Taxonomic Units (OTUs) can be extracted from eDNA metabarcoding. However, the extent to which the diversity of OTUs provided by a limited eDNA sampling effort can predict reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 3 publications
(3 reference statements)
3
26
0
Order By: Relevance
“…This unexpected result suggests that there may be an upper limit to the amount of diversity eDNA can capture within a single liter of seawater. As such, eDNA studies in high diversity ecosystems will require much greater sampling intensity, a result consistent with Juhel et al (2020). Given that our models indicate that high biodiversity regions like Raja Ampat may require in excess of 300 one-liter samples to capture all fish diversity present, eDNA surveys in high diversity areas will either need to increase the numbers of samples or volume of water per sample to be maximally informative.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This unexpected result suggests that there may be an upper limit to the amount of diversity eDNA can capture within a single liter of seawater. As such, eDNA studies in high diversity ecosystems will require much greater sampling intensity, a result consistent with Juhel et al (2020). Given that our models indicate that high biodiversity regions like Raja Ampat may require in excess of 300 one-liter samples to capture all fish diversity present, eDNA surveys in high diversity areas will either need to increase the numbers of samples or volume of water per sample to be maximally informative.…”
Section: Discussionsupporting
confidence: 61%
“…Similarly, most coral reef eDNA studies to date have occurred in Japan, Central Pacific, Western Australia, and the Red Sea (Alexander et al 2020;Bessey et al 2020; DiBattista et al 2017; Lafferty et al 2020; Oka et al 2020;Stat et al 2017; Stat et al 2019; West et al 2020), where fish biodiversity is far lower than the Coral Triangle (Bellwood & Meyer, 2009; Roberts et al, 2002). Most recently, Juhel et al (2020) used eDNA to examine fish diversity in Raja Ampat, Indonesia, home to the world’s most diverse reef fish fauna (Allen, 2002), reporting a strong correlation between eDNA results and checklists from visual data. However, species accumulation curves indicated that eDNA greatly under sampled species diversity, suggesting that the methods, sampling design, and bioinformatics approaches employed in temperate eDNA studies may not be equally effective in megadiverse tropical regions like the Coral Triangle.…”
Section: Introductionmentioning
confidence: 99%
“…We performed the aggregation into MOTUs using the teleo primers, as the bioinformatics clustering pipeline using SWARM has only been developed and fully tested with this primer (Juhel et al., 2020; Marques et al., 2020). In Providencia, the eDNA clustering pipeline identified 227 distinct MOTUs, and we detected an average of 26.2 ± 12.6 MOTUs per filter.…”
Section: Resultsmentioning
confidence: 99%
“…eDNA metabarcoding is now widely employed in various aquatic ecosystems (Deiner et al., 2017), but some uncertainties remain as regard to sampling design (Valentini et al., 2016) and the choice of markers (Collins et al., 2019; Stat et al., 2017) and bioinformatics pipeline (Calderón‐Sanou et al., 2020; Juhel et al., 2020). We tested three different primer sets for the 12S region looking for fish taxa, but we did not find a universal marker able to detect all taxa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation